Evaluation of flue gas desulfurization gypsum as a low-cost precipitant for phosphorus removal from anaerobic digestion effluent filtrate - Guo, Yaping; Khalaf, Adam; Kong, Wenzhuo; Ma, Hongzhen; Liang, Jiawei; Zhao, Dongxu; Wang, Zhiguo; Li, Yebo; Xu, Fuqing (International Journal of Agricultural and Biological Engineering, 2024)
Land application of anaerobic digestion (AD) effluent as a fertilizer is desirable for nutrient recycling, but often supplies excess phosphorus (P), which contributes to surface water eutrophication. Reducing the P content in AD effluent filtrate using calcium (Ca) treatment prior to land application is a potential strategy for improving effluent disposal and meeting the discharge standard. This study took flue gas desulphurization (FGD) gypsum, a by-product of coal-fired power plants, as a low-cost Ca source, and combined with traditional phosphorus removal agents to achieve high phosphorus removal efficiency with less chemical cost. As the results showed, FGD gypsum dosages of 20 mmol/L Ca (3.44 g/L) and 40 mmol/L Ca (6.89 g/L) removed up to 97.1% of soluble P (initially 102.8 mg/L) within 60-90 minutes. Combining FGD gypsum treatment with traditional chemical treatments using calcium hydroxide [Ca(OH)2] or ferric chloride (FeCl3) could achieve >99% P removal with reduced chemical costs. This study demonstrated that FGD gypsum is an efficient calcium-based precipitant for phosphorus removal, offering a cost-effective and sustainable approach to enhance wastewater treatment practices and meet discharge standards in wastewater management. Key words: flue gas desulfurization gypsum; anaerobic digestion effluent; precipitation; phosphorus removal; eutrophicationDOI: 10.25165/j.ijabe.20241704.8227Citation: Guo Y P, Khalaf A, Kong W Z, Ma H Z, Liang J W, Zhao D X, et al. Evaluation of flue gas desulfurization gypsum as a low-cost precipitant for phosphorus removal from anaerobic digestion effluent filtrate. Int J Agric & Biol Eng, 2024; 17(4): 198–206.